2012
DOI: 10.3109/02813432.2012.732469
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for not reporting patient safety incidents in general practice: A qualitative study

Abstract: The results suggest that the visions of formal, comprehensive, and systematic reporting of (and learning from) patient safety incidents will be quite difficult to realize in general practice. Future studies should investigate how various ways of organizing incident reporting at the regional level influence local activities of reporting and learning in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 19 publications
4
31
0
1
Order By: Relevance
“…This implies that a health worker would never report an incident when he/she is not sure of its consequences which can include a legal punishment, being terminated from the job and putting a copy of a letter in one's file. These are in agreement with previous reports [12,14,21,28,31,34]. Although this study was conducted in a single regional referral hospital, its results could to some degree be generalizable to the other settings considering the fact that the healthcare system and curriculum of healthcare professionals is similar across the country.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that a health worker would never report an incident when he/she is not sure of its consequences which can include a legal punishment, being terminated from the job and putting a copy of a letter in one's file. These are in agreement with previous reports [12,14,21,28,31,34]. Although this study was conducted in a single regional referral hospital, its results could to some degree be generalizable to the other settings considering the fact that the healthcare system and curriculum of healthcare professionals is similar across the country.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have explored the barriers to incident reporting in healthcare settings [3-11]. These barriers are associated with various characteristics at the organizational and individual levels [8].…”
Section: Introductionmentioning
confidence: 99%
“…Braithwaite et al [4] suggested that the most frequently encountered barriers to reporting incidents are culturally embedded. Kousgaard et al [3] found that the major reasons for low reporting rates were related to a perceived lack of practical usefulness, issues of time and effort in busy situations, and consideration of other professionals involved.…”
Section: Introductionmentioning
confidence: 99%
“…A study exploring the reasons for poor reporting of patient safety incidents in the Danish Primary Healthcare (PHC) setting13 established that the main deterrents were time constraints and a perceived sense of futility. This was despite the process of reporting patient safety incidents having been made mandatory in Denmark's PHC sector 2 years previously 13.…”
Section: Introductionmentioning
confidence: 99%
“…This was despite the process of reporting patient safety incidents having been made mandatory in Denmark's PHC sector 2 years previously 13. This lack of understanding as to how the process can, if effectively undertaken, reduce the likelihood of an error or injury being repeated was also alluded to in a qualitative investigation of subject matter experts from a range of high-risk professions, including healthcare, in the UK 14.…”
Section: Introductionmentioning
confidence: 99%